The Effect of Product Prices and Promotions on Purchasing Decisions of Mitsubishi Brand Cars at PT. Srikandi Diamond Motors, Tangerang Branch - Ahmad Nurhadi (PINISI Discretion Review, 2020)
This study aims to determine the effect of product prices and promotions on purchasing decisions of Mitsubishi brand cars at PT. Srikandi Diamond Motors Tangerang Branch. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the price of products significantly influence the decision to purchase a Mitsubishi brand car by 42.7%, the hypothesis test obtained significance of 0,000 <0.05. Promotion has a significant effect on the decision to purchase a Mitsubishi brand car of 43.1%, the hypothesis test obtained a significance of 0,000 <0.05. Product prices and promotions simultaneously have a significant effect on purchasing decisions of Mitsubishi brand cars by 53.5%, hypothesis testing obtained significance of 0,000 <0.05.